Pengaruh Model PBL Berbantuan Alat Peraga Terhadap Hasil Belajar Materi Sistem Peredaran Darah Manusia - Zulfa Ulin Nuha; Ira Nurmawati (JURNAL ILMIAH NUSANTARA, 2025)
One of the problems in learning in schools is the low learning outcomes of students. This can be seen from the initial data of students' daily scores which are still below the KKM. The human circulatory system requires an appropriate model because of the abstract and complex nature of the material. Therefore, the application of the problem based learning model assisted by teaching aids is very much needed. This study aims to determine the Effect of the PBL Model Assisted by Teaching Aids on Learning Outcomes of the Human Circulatory System Material. Quantitative research method with Quasi Experimental Design research type, Sampling technique using Purposive Sampling obtained the sample population, namely students of class XI MIPA 2 as the experimental class and XI MIPA 3 as the control class. Data collection techniques in the form of (1) observation (2) documentation (3) tests in the form of pretest-posttest. Data analysis techniques using the normality test with Shapiro Wilk, and the Mann Whitney U-Test test. The results of the study showed that there was a significant influence of the PBL model assisted by teaching aids on learning outcomes of the human circulatory system material, namely based on the results of the Mann Whitney U-Test on the posttest results obtained a Sig. value. two tail of 0.000 < 0.05.